A new species of the spider genus Taranucnus from Ukraine (Araneae, Linyphiidae) - Gnelitsa, Valery A. (Zootaxa, 2016)
Currently the linyphiid genus Taranucnus includes four species: T. setosus (O. P.-Cambridge, 1863), the type species with Palearctic distribution, T. bihari Fage, 1931 (Eastern Europe), T. nishikii Yaginuma, 1972 (Japan) and T. ornithes (Barrows, 1940)(USA). In Ukraine Taranucnus is represented by two species, T. setosus and T. bihari. A detailed study of the male mentioned earlier as Taranucnus sp. (Chumak, Prokopenko & Tymochko 2007; Prokopenko, Chumak 2007), and several females close to T. bihari Fage, 1931 revealed a new species of this genus. Since it is hard to clarify the position of some of these females we report them below as T. cf. bihari.